Therapeutic applications and antibacterial and antifungal activities of Syzygium cumini (L.) Skeels extracts: a systematized literature review focusing on dental applications - Figueirêdo Júnior, Ernani Canuto; Costa, Bruna Palmeira; Freire, Julliana Cariry Palhano; Melo, Waleska Ohana de Souza; Ferreira de Araújo, Cristina Ruan; Costa, Edja Maria Melo de Brito; Pereira, Jozinete Vieira (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Medicinal plants are an important source of curative substances for the treatment of diseases. Investigations are focusing particularly on medicinal plants used to treat affections of the oral cavity. Among these species, there is evidence of potential applications of Syzygium cumini to dentistry. The objective of this systematized literature review was to synthesize the evidence on the antimicrobial activity of this plant, as well cite some as the traditional uses of its extracts for dental purposes. The data indicate that the extracts prepared from different parts of the plant have antibacterial and antifungal effects on different pathogenic microorganisms of the oral microbiota and/or those that can potentially cause oral diseases, demonstrating a promising therapeutic potential for indication and use in Dentistry to prevent and/or treat oral affections.